Thrombozytose und Thrombozytopenie – Ursachen und klinische Bedeutung - Wille, Kai; Sadjadian, Parvis; Griesshammer, Martin (DMW - Deutsche Medizinische Wochenschrift, 2017)
Due to the central role of platelets in hemostasis, the clinical relevance of quantitative changes in platelet counts (< 150 G/l or > 450 G/l) may be significant. Thrombopoesis (= production of platelets) occurs in the bone marrow, and the hormone thrombopoetin takes control on its regulation.In thrombocytosis, primary causes have to be distinguished from the far more common reactive (= secondary) reasons. The most important form of primary thrombocytosis occurs in myeloproliferative neoplasms especially in essential thrombocythemia (ET). Clinically, increased thrombophilia, microcirculatory disturbances as well as an increased hemorrhagic diathesis occur in patients with myeloproliferative neoplasms. According to the WHO diagnosis criteria 2016 standard diagnostic procedure in myeloproliferative neoplasms includes bone marrow biopsy and the detection of one of the acquired and typical MPN mutations in the JAK2, MPL or CALR gene.In contrast, patients with thrombocytopenia more often suffer from bleeding complications, however, in antiphospholipid syndrome or thrombotic microangiopathy (TMA) thrombotic events occur in spite of a low platelet count. Generally it makes sense to differentiate between pathological changes in thrombopoesis and the various causes of increased peripheral platelet turnover. Concerning differential diagnosis a careful anamnesis is very important in order to get hints like drugs associated with thrombocytopenia, signs of infection or autoimmune disorders. As an initial diagnostic approach we recommend examination of the blood smear in order to exclude pseudothrombocytopenia or disorderes like thrombotic microangiopathy, myelodysplasia or other hematological diseases.
Keywords: Thrombopenie; Thrombozytose; chronisch myeloproliferative Neoplasien; Essentielle Thrombocythämie